Identifying the Driving Forces Affecting the Development of the Government's Revenue Portfolio - Esmailizadeh, Sattar; Makvandi, Foad; Kiani, Ezatollah; Chenari, Vahid; Amirnejad, Ghanbar (Management Strategies and Engineering Sciences, 2025)
The present study aims to formulate policies for developing the government's revenue portfolio using a futures research approach. This research seeks to identify and explore possible futures and scenarios for the development of the government's revenue portfolio and strives to formulate strategies based on the most desirable scenarios. The study falls within the domain of futures research and is classified as qualitative research, utilizing the scenario-writing method. The statistical population of this study includes "experts in the fields of economics and policymaking" categorized into three groups: (a) academic elites, (b) economic managers and decision-makers, and (c) economic decision-makers in parliament. After selecting the experts, a structured inquiry process was conducted to collect their views regarding the government's revenue portfolio. Ultimately, after screening the variables, 84 variables were identified within eight dimensions as the primary macro variables affecting the government's revenue portfolio: legal factors, cultural and social factors, economic factors and sub-sectors, global and international factors, structural factors, banking and financial factors, science and knowledge-related factors, and political factors. Subsequently, using the cross-impact analysis (structural analysis) method through MICMAC software, the key influencing factors shaping the future state of the studied environment were analyzed. Based on this analysis, the key influencing variables affecting the development of the government's revenue portfolio include natural gas and petrochemical industries, agricultural economy, inflation rate, labor market conditions and employment levels, stock prices and stock exchange performance, free trade zones, tax return conditions and amounts, consumption tax rates, interest rates, non-financial government revenues, locomotive industry, heavy industries (steel, electricity, and automobile manufacturing), income tax rates, tariffs and various production and employment barriers, traffic economy, foreign investment inflows, housing market conditions and prices, textile industries, construction and urban development, unemployment rate, and government revenues from natural resources.